The Ant Genus Oxyopomyrmex Wheeler (Formicidae, Myrmicinae) from the Peninsula Iberica: Two New Species and New Distributional Data - Joaquín L. Reyes-López (Insects)
Two new species of the genus Oxyopomyrmex are described from Spain (Iberian Peninsula). The first belongs to the magnus group—characterized by a head more wide than long—and is distinguished by strongly developed cephalic striations, pale coloration (light brown) and a relatively small body size. To date, it has been recorded in the provinces of Jaén and Granada. The second species is even smaller in size, with very faint cephalic striations and short, triangular propodeal spines—morphological features that clearly set it apart from all previously known species. Its current distribution appears to be restricted to the province of Huelva, near the Atlantic coast, including the iconic Doñana National Park. With these additions, the number of Oxyopomyrmex species known from Spain increases from two to four. To date, sampling efforts have only focused on the southern part of the country, suggesting that additional, undiscovered species may still exist.